Jane Tolmach for Assembly 36th District Press Release (1976)
In this October 13, 1976 press release, Assembly candidate Jane Tolmach charges that more than 75% of her Republican opponent's campaign funding comes from special interest groups outside Ventura County. She cites approximately $22,000 in contributions since June from organizations and corporate political action committees, including real estate, building industry, agricultural, and corporate interests. Tolmach questions whether these donors expect special treatment in return and criticizes the group "United for California" as a vehicle for anonymous contributions. She calls on her opponent to fully disclose all contributors and any commitments made in exchange for financial support.